The LACE Index: A Predictor of Mortality and Readmission in Patients With Acute Myocardial Infarction. Issue 5 (September 2021) - Labrosciano, Clementine; Tavella, Rosanna; Air, Tracy; Zeitz, Christopher J.; Worthley, Matthew; Beltrame, John F.
ABSTRACT: Introduction: Improving patient outcomes after acute myocardial infarction (AMI) may be facilitated by identifying patients at a high risk of adverse events before hospital discharge. We aimed to determine the accuracy of the LACE (Length of stay, Acuity, Comorbidities, Emergency presentations within prior 6 months) index score (a prediction tool) for predicting 30-day all-cause mortality and readmission rates (independently and combined) in South Australian AMI patients who had an angiogram. Methods: All consecutive AMI patients enrolled in the Coronary Angiogram Database of South Australia Registry at two major tertiary hospitals and discharged alive between July 2016 to June 2017. A LACE score was calculated for each patient, and receiver operating characteristic curve analysis was performed. Results: Analysis of registry patients found a 30-day unplanned readmission rate of 11.8% and mortality rate of 0.7%. Moreover, the LACE index was a moderate predictor (C-statistic = 0.62) of readmissions in this cohort, and a score ≥10 indicated moderate discriminatory capacity to predict 30-day readmissions. Conclusion: The LACE index shows moderate discriminatory capacity to predict 30-day readmissions and mortality. A cut-off score of nine to optimize sensitivity may assist clinicians in identifying patients at a high risk of adverse outcomes.